Rethinking the Postwar International Migration Regime from the Global South: Venezuela in a Global History of White Immigration. Issue 2 (August 2022) - Huhn, Sebastian
Abstract: Between 1947 and early 1952, the International Refugee Organization (IRO), which was established within the framework of the United Nations to "solve" the so-called European refugee problem after the end of the Second World War, resettled one million European refugees—victims of Nazism as well as East European refugees who escaped the Red Army—all over the world. The IRO's resettlement project is regarded as a blueprint for the establishment of the postwar international migration regime, and it was the predecessor of later initiatives such as the United Nations High Commissioner for Refugees (UNHCR). In this article I argue that the IRO's history as well as the history of the migration regime after the Second World War has, thus far, mainly been written from the perspective of U.S. American and European history. Northern nations are considered agents in this history, while southern countries are considered as passive "destinations." In the case of Venezuela, the article argues that the Global South's active role in the migration regime must be taken into consideration to understand postwar migration. From the perspective of a connective approach to global history, it shows how Venezuela, as a political agent, was involved in shaping the migration regime; how it perceived itself as an agent within that regime; and how it intervened on a small scale to shape its form and function.